Contemporary student politics in Bangladesh: Impacts, trends, and insights from the University of Rajshahi - Barik, Md. Abdul; Nahar, Mst. Quamrun; Arafat, Md. Yeasir (Privietlab, 2026)
The increase in student politics helps students gain leadership power and become aware. However, university campuses are being contaminated with violence, party interests, personal benefits, and more. Student politics has both negative and positive impacts on society. This study, which is based on primary data gathered from 100 respondents at the University of Rajshahi, aims to examine the role of student politics in Bangladesh from July 2024 to date, to know people’s opinion about student politics, to assess the impact of student politics on academic and governance activities, and to identify the positive and negative aspects of student politics. A purposive sampling method was used. The study shows two sides of the coin on students’ politics: On one side of the coin, it makes the student leader politically aware. However, it hampers the normal functioning of educational institutions, creating administrative problems, violence, and many more. The researchers have offered some practical recommendations for reform at the end of the study for student politics to uphold a positive role in democracy and institutions, and the significance of democratization, transparency, and accountability.